Literasi sains : implikasi sosio-budaya ke atas masyarakat islam - Hashim, Rosnani (Yayasan Takmir, 2008)
This article discusses the status and harmonious relations between science and religion within the Islamic Tradition. It provides a definition of scientific or science literacy. It argues for the importance of scientific litercay and the scientific mind, in particular among Muslims and propose a few approaches in inculcating this scientific mind. It argues that science can help Muslims fulfill ther role as Khalifatullah (vicegerent of Allah). It concludes with proposing the various methods to foster science literacy, foremost of which is the proper reading of the Qur'an and going back closer to nature that surrounds men.